Comparing vaccination coverage of American Indian children with White children in North Dakota. (September 2020) - Woinarowicz, Mary; Howell, Molly
Abstract: Objectives: The objective of this study was to compare immunization rates of American Indian (AI) and White children in North Dakota and identify disparities in immunization rates by race. Study design: The study design was to assess immunization coverage rates by race using immunization information system (IIS) data. Methods: Data from the North Dakota Immunization Information System (NDIIS) for children aged 19–35 months during quarter four of 2014, 2015, 2016, 2017 and 2018 were used to assess and compare immunization coverage rates for AI and White children. NDIIS data were also analyzed for timeliness of vaccine administration, Vaccines for Children (VFC) status, and the number of doses still needed to be considered up to date (UTD) with routinely recommended immunizations. Results: In quarter four of 2018 (Q4 2018), only 60% of AI children were UTD with the complete 4:3:1:3:3:1:4 vaccine series compared with 74.5% of White children of the same age. Fewer VFC-eligible AI children (59.1%) are UTD than VFC-eligible White children (68.7%). AI children were also more likely to be delayed at each immunization milestone, leading to fewer AI children to be UTD by 19 to 35 months of age. Conclusions: This study shows that there is a racial disparity in immunization coverage rates between AI and White children in North Dakota. Public health and private healthcare providers should work to identify and address barriers to vaccination and should implement strategies to increase immunization rates for AI children. Highlights: Fewer American Indian (AI) children in North Dakota were up-to-date (UTD) with routinely recommended immunizations compared with White children. Fewer Vaccines for Children (VFC)-eligible AI children were UTD than VFC-eligible and Not-VFC-eligible White children. More AI children were delayed at each immunization milestone, leading to fewer AI children UTD by 19–35 months of age.